1999
DOI: 10.1021/np980447+
|View full text |Cite
|
Sign up to set email alerts
|

Massarinolins A−C:  New Bioactive Sesquiterpenoids from the Aquatic Fungus Massarina tunicata

Abstract: Massarinolins A-C (1-3), three new bioactive sesquiterpenoids possessing rare ring systems, have been isolated from liquid cultures of the aquatic fungus Massarina tunicata Shearer & Fallah. The structures were determined primarily by analysis of NMR data. Metabolites 1-3 are the first compounds to be reported from any member of the genus Massarina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 18 publications
3
67
0
Order By: Relevance
“…Six of the marine Massarina species were described from mangroves (Hyde et al, 1992), while two were described from the salt marsh plant Juncus roemerianus (Kohlmeyer et al, 1995a,b). The secondary metabolite chemistry of Massarina species is virtually unexplored; only one freshwater species, M. tunicata Shearer and Fallah, has been investigated and eleven new bioactive compounds have been recorded (Oh et al, 1999(Oh et al, , 2001(Oh et al, and 2003. Although limited data are available, these studies indicate that Massarina species are chemically productive.…”
Section: Introductionmentioning
confidence: 99%
“…Six of the marine Massarina species were described from mangroves (Hyde et al, 1992), while two were described from the salt marsh plant Juncus roemerianus (Kohlmeyer et al, 1995a,b). The secondary metabolite chemistry of Massarina species is virtually unexplored; only one freshwater species, M. tunicata Shearer and Fallah, has been investigated and eleven new bioactive compounds have been recorded (Oh et al, 1999(Oh et al, , 2001(Oh et al, and 2003. Although limited data are available, these studies indicate that Massarina species are chemically productive.…”
Section: Introductionmentioning
confidence: 99%
“…5 It shows biological activity against Bacillus subtilis (ATCC 6501) and Staphylococcus aureus (ATCC 29213). It appears to be biosynthesized from a farnesyl-type precursor and even though its relative stereochemistry was deduced by spectroscopic methods its absolute stereochemistry remains a challenge for synthetic chemists.…”
Section: Introductionmentioning
confidence: 99%
“…Among fungi from the diverse environments, the freshwater aquatic fungi have received attention from the scientific community. Consequently several groups of investigators have identified that freshwater fungi contain some unique biologically active metabolites such as decaspirones (Jiao et al, 2006), gliocladines (Dong et al, 2005), resorcylides (Dong et al, 2007), pseudohalonectrins (Dong et al, 2006), massarinolins (Oh et al, 1999), ophiocerins (Reátegui et al, 2005), massarigenins (Oh et al, 2003) etc. There may be many more freshwater fungi, not yet tested, which could prove to be a fruitful source of biologically active secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%